Molnik pri Ljubljani v starejši železni dobi = The Iron Age site at Molnik near Ljubljana - Tecco Hvala, Sneža (Opera Instituti Archaeologici Sloveniae, 2017)
Molnik is a hill in the hinterland of Ljubljana in central Slovenia that has been known as an archaeological site for quite some time. Systematic investigations ensued in the 1980s and 1990s, led by Ivan Puš, then curator in the Mestni muzej Ljubljana. They revealed ramparts and habitation terraces on the summit of the hill, as well as flat and tumulus graves on five locations around the summit that date to the Early Iron Age and some finds from later periods.